2016
DOI: 10.1053/j.gastro.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of Helicobacter pylori–Induced Gastric Cancer

Abstract: Colonization of the human stomach by Helicobacter pylori and its role in causing gastric cancer is one of the richest examples of complex relationship among human cells, microbes, and their environment. It is also a puzzle of enormous medical importance given the incidence and lethality of gastric cancer worldwide. We review recent findings that have changed how we view these relationships and affected the direction of gastric cancer research. For example, recent data indicate that subtle mismatches between ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
557
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(597 citation statements)
references
References 149 publications
(176 reference statements)
2
557
2
9
Order By: Relevance
“…Over 80% of individuals infected with the bacterium are asymptomatic, and it may play an important role in the natural stomach ecology 1 . More than 50% of the world's populations have H. pylori in their upper gastrointestinal tract 2 . Infection is more common in developing countries than Western countries 3 .…”
Section: Helicobactermentioning
confidence: 99%
“…Over 80% of individuals infected with the bacterium are asymptomatic, and it may play an important role in the natural stomach ecology 1 . More than 50% of the world's populations have H. pylori in their upper gastrointestinal tract 2 . Infection is more common in developing countries than Western countries 3 .…”
Section: Helicobactermentioning
confidence: 99%
“…It is well established that atrophy of the corpus mucosa, leading to decreased acid secretion, is highly associated with GC development. How the chronic infection and inflammation lead to cancer in some individuals but leave the majority without symptoms is still not outlined but is thought to depend on a combination of host susceptibility, environmental factors, and bacterial pathogenicity (14).…”
mentioning
confidence: 99%
“…[1,2] The overall 5-year survival rate of GC patients is only between 15 to 35%. [3] Epidemiological studies show that persistent Helicobacter pylori (H. pylori) infection accounts for approximate 75% of confound risk factors for GC.…”
Section: Introductionmentioning
confidence: 99%
“…pylori, a gram-negative spiral-shaped pathogenic bacterium, specifically colonizes and induces damage to the gastric epithelium leading to chronic gastritis, ulcers and even cancer. [2,7,8] Considerable studies have demonstrated that a mixed response of Th1 and Th17 cells plays a critical role in H. pylori-induced inflammatory gastric diseases and cancer. [9,10] The phenotypes of T helper subsets are determined by the local cytokine milieu and their lineage-specific transcription factors.…”
Section: Introductionmentioning
confidence: 99%